Epidemiological profile of malignant bone and cartilage neoplasms in Brazil from 2013 to 2023 (Research, Society and Development, 2025)
Introduction: Neoplasia of bones and articular cartilage is a disease caused by the exaggerated proliferation of bone and cartilage cells, especially in young age groups, due to bone growth and greater activity of these cells. Objective: This article aims to analyze the frequency and distribution of bone and articular cartilage cancer in Brazil, in the period between 2013 and 2023. Methodology: This epidemiological article used a quantitative approach, carried out from data collected in DATASUS/ Tabnet. Results: During the period analyzed, 30,472 cases of malignant neoplasia in bones and joint cartilage were notified, with the Southeast being the region with the highest incidence of this disease. The groups with the highest number of diagnoses were elderly people aged 60 to 69 and young people aged 10 to 19. Conclusion: The discussion of this study highlights the need to create ways to detect bone and articular cartilage cancers more quickly and, therefore, prevent the progression of the disease and facilitate the remission of patients throughout Brazil.